Unmanned aerial system (UAS) for monitoring and communication in IBS construction project / Anis Sofea Mad Said and Wan Akmal Zahri Wan Zaharuddin - Mad Said, Anis Sofea; Wan Zaharuddin, Wan Akmal Zahri (2019)
Industrial Revolution 4.0 (IR) is changes in work, workers, management and cycle of work by using technology. Industrialized Building System (IBS) construction management in site can be improve by applying IR 4.0. The problems in managing of IBS project arise from the practice of manually monitoring the Precast Concrete (PC) components arrived at the site which is tedious and susceptible to human error. In addition, the problem of communication by signal person to crane operator in PC components assembling can be misinterpret. The purpose of this research is to identify the problems of IBS management onsite and to propose Unmanned Aerial System (UAS) for Monitoring and Communication (UMAC). The method used in this research are by desk study and simulation to gain the information and performance. The result is gained by simulation and differentiate the performance of UAS in market and the application in construction site. For the conclusion, Application of UMAC in IBS construction give benefits in systematic practice and use of technology in solving problems.